Enhancing teacher performance through competence and work discipline: The mediating role of work motivation - Nilnal Muna; Siti Nur Azizah; Feby Evelyna; Aris Susetyo (Trigin Publisher, 2025)
The study was conducted to analyze the influence of teacher competence and work discipline on teacher performance through work motivation as an intervening variable at SMK Muhatammadiyah Kutowinangun. This research is a descriptive quantitative design, using 46 teachers as respondents by distributing questionnaires. This model used path analysis and data management tools, such as SPSS for Windows 25. The results of the study showed that competence and work discipline had a positive effect on work motivation. Competence, discipline, and work motivation had a positive impact on teacher performance. Work motivation mediates the influence of competence and work discipline on teacher performance. This finding provides an important contribution to the development of motivation theory, as well as being a practical reference for organizations in forming teacher discipline and competence.